A CFD modelling study of multi-phase flow behaviour of biomass and biochar particles in a bubbling fluidized bed - Sharma, Abhishek; Pareek, Vishnu; Utikar, Ranjeet; Wang, Shaobin; Yang, H.; Zhang, D. (CSIRO, 2012)
Biomass is a promising renewable energy source worldwide. Several modelling and experimental studies have been conducted for biomass thermo-chemical degradation processes, of which, pyrolysis is a significant one due to formation of a variety of products at lower temperature conditions. However, there has not been sufficient information about the hydrodynamics of this process. It is essential to examine the segregation and mixing of different phases in a reactor during biomass pyrolysis. In this work, a multi-phase CFD model for the poly-disperse behavior of biomass in the presence of biochar as bed material in a bubbling fluidized bed has been developed. According to results, the biomass particles behaved as flotsam, while biochar particles behaved as jetsam in the bed. The sensitivity analysis of the effects of operating parameters such as the superficial gas velocity, biomass particle density and diameter on the fluidization behaviour was also conducted.